Nanocarriers for skin delivery of cosmetic antioxidants - Lucia Montenegro (GarVal Editorial Ltda., 2014)
The demand of natural skin care products is steadily growing since consumers perceive them as safe. Currently, cosmetic manufacturers are focusing their efforts on developing innovative natural products to address skin-aging signs, thus meeting consumers' needs of healthy appearance and well-being. To prevent or treat skin aging, topical supplementation with antioxidant is regarded as one of the most promising strategies. However, most antioxidants presently used in skin care formulations show unfavorable physicochemical properties such as excessive lipophilicity or hydrophilicity, chemical instability and poor skin penetration that actively limit their effectiveness after topical application. Therefore, nanocarriers such as liposomes, niosomes, microemulsions and nanoparticles have been widely investigated as delivery systems for antioxidants to improve their beneficial effects in the treatment of skin aging. In this article, the antioxidants most commonly used in anti-aging cosmetic products will be reviewed along with the nanocarriers designed to improve their safety and effectiveness.